Precision Molecular Pathology of Uterine Cancer - Deavers, Michael T.; Coffey, Donna M. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive review for practicing pathologists to understand the molecular biology, diagnostics, and predictive markers and implications for therapy of uterine cancer. While molecular based therapeutic strategies for uterine cancer are not as well developed as for some other organ sites, these are the most common gynecologic malignancies and there have been many important recent developments that are discussed in this volume. Comprehensive chapters address essential information about endometrial carcinoma, uterine mesenchymal tumors, and cervical carcinoma and include the pathogenesis of carcinoma and discuss molecular based classification, biomarkers, therapy, prevention, and hereditary cancers of the uterus. Precision Molecular Pathology of Uterine Cancer is a unique and one of a kind resource for practicing pathologists, pathologists in training and gynecologists.
Keywords: Medicine.; Gynecology.; Oncology.; Pathology.; elektronické knihy; electronic books